Documents relating to the palestine problem - Jewish Agency for Palestine (London : Jewish Agency for Palestine, 1945)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: zionisme; joodse staat; Palestijnse kwestie; Palestina; Midden-Oosten.